PENGARUH KOMUNIKASI INTERPERSONAL ORANG TUA DAN ANAK TERHADAP PRESTASI BELAJAR SISWA KELAS X - Muhammad Rofik; Agus Saifuddin Amin (Hudan Lin Naas: Jurnal Ilmu Sosial dan Humaniora, 2021)
Interpersonal communication is one of communication methods that often used for communicates with others, no doubt. The success of parents and teachers in communicating are the important one. Because they are humans that we should imitated. According to explanation above, the writer can take three conclusions from this research are:Based on this research to know available or not the influencw of interpersonal communication of parents to the achievement of students of class I MA Nurul Huda Pangilen Dasuk Sumenep Year 2017/2018, it can be shown by Thitung X1 2.589 > Ttabel 2.026. Hence thus the working hypothesis (H1) which states that "there is influence interpersonal communication parent to learning achievement Class I MA Nurul Huda Pangeling Dasuk Sumenep 2017/2018" otherwise accepted. Based on the above research to find out whether or not the influence of interpersonal communication of children to the achievement of students of class I MA Nurul Huda Pangilen Dasuk Sumenep Year 2017/2018, it can be shown Thitung X2 sebesar 1.361 < Ttabel 2.026. Thus it is proven working hypothesis (H1) which states that "there is influence of parents' internal communication on learning achievement Class. According to the research above, knowing there is or not the effect of interpersonal communication between parents and children's achievement for student grade 1 MA (Islamic Senior High School) Nurul Huda pangilen Dasuk Sumenep 2017/2018. So, it can be counted as (Fhitung 4.834 > Ftabel 3.25). So that way, it's been approved that work hypothesis (H1) which said that 'the effect of interpersonal communication between parents and children's achievement for student grade 1 MA Nurul Huda Pangeling Dasuk Sumenep 2017/2018 is accepted'From this research, it's concluded that the effect of interpersonal communication between parents and children's achievement for student grade 1 MA Nurul Huda Pangilang Dasuk Sumenep 2017/2018  accounted into medium category.